2016
DOI: 10.1073/pnas.1516631113
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and small-molecule stabilization of the multisite tandem binding between 14-3-3 and the R domain of CFTR

Abstract: Cystic fibrosis is a fatal genetic disease, most frequently caused by the retention of the CFTR (cystic fibrosis transmembrane conductance regulator) mutant protein in the endoplasmic reticulum (ER). The binding of the 14-3-3 protein to the CFTR regulatory (R) domain has been found to enhance CFTR trafficking to the plasma membrane. To define the mechanism of action of this protein–protein interaction, we have examined the interaction in vitro. The disordered multiphosphorylated R domain contains nine differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
142
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 55 publications
14
142
0
Order By: Relevance
“…Indeed, binding of FC to a non-MODE III motif has been reported also for the cystic fibrosis transmembrane conductance regulator (CFTR). However, in this case, FC binds in its standard conformation, which is made possible by the specific global architecture of the CFTR:14-3-3 complex (Stevers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, binding of FC to a non-MODE III motif has been reported also for the cystic fibrosis transmembrane conductance regulator (CFTR). However, in this case, FC binds in its standard conformation, which is made possible by the specific global architecture of the CFTR:14-3-3 complex (Stevers et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…More recently it has been shown that fusicoccane derivatives can also stabilise internal or ‘mode 1 or 2’ partner protein recognition motifs. For example FC‐A has been shown to stabilize the 14‐3‐3 interaction with CFTR , the semi‐synthetic derivative ISIR‐005 stabilizes the interaction with Gab2 and related natural product cotylenin the interaction with C‐Raf .…”
mentioning
confidence: 99%
“…with previous examples, [23,27] by connecting two more weakly binding monovalent ExoS motifs with aflexible linker,which resulted in over 100-fold affinity enhancement (see Figure 2 in the Supporting Information). In the absence of Q8, the FGG-ERa peptide was observed to displace the ExoS peptide with an IC 50 value of 1.0 mm ( Figure 2B,b lack line).…”
mentioning
confidence: 54%
“…[21] They are dimerized proteins that typically bind their partner proteins through short, phosphorylated motifs [22] either at two single-motif binding sites or at atandem binding site,which greatly enhances the binding affinity. [23] Whereas PPIs with the 14-3-3 monomer can be modulated by natural products, [23] peptide derivatives, [22,24,25] synthetic molecules, [26] or supramolecular ligands, [3] molecular approaches to control the valency of 14-3-3-protein complexes are currently absent. Therefore,werationally designed abinary bivalent supramolecular assembly platform based on cucurbit [8]uril and dimeric adapter protein 14-3-3.…”
mentioning
confidence: 99%